ChemInform Abstract: Alternative One‐Pot Synthesis of (Trifluoromethyl)phenyldiazirines from Tosyloxime Derivatives: Application for New Synthesis of Optically Pure Diazirinylphenylalanines for Photoaffinity Labeling. Issue 25 (5th June 2015) - Wang, Lei; Murai, Yuta; Yoshida, Takuma; Ishida, Akiko; Masuda, Katsuyoshi; Sakihama, Yasuko; Hashidoko, Yasuyuki; Hatanaka, Yasumaru; Hashimoto, Makoto
Abstract: Diazirines (II) are formed from tosyloxime derivatives (I) via the deprotonation of intermediate diaziridine by NH2 ‐ generated from liquid NH3 .